Religion, spirituality and personal recovery among forensic patients. Issue 3 (7th August 2019) - Glorney, Emily; Raymont, Sophie; Lawson, Amy; Allen, Jessica
Abstract : Purpose: Religion and spirituality are well-researched concepts within the field of psychology and mental health yet they have rarely been researched in high-secure services within the UK. Research in mental health and prison contexts suggests benefits of religion/spirituality to coping, social support, self-worth, symptoms of depression and anxiety and behavioural infractions. The purpose of this paper is to investigate the role of religion/spirituality in high-secure service users' personal recovery. Design/methodology/approach: Semi-structured interviews were carried out with 13 male patients in a high-secure hospital, with primary diagnoses of mental illness ( n =11) or personality disorder ( n =2). Participants were from a range of religious/spiritual backgrounds and were asked about how their beliefs impact their recovery and care pathways within the hospital. Data were analysed using interpretative phenomenological analysis. Findings: Three superordinate themes were identified: "religion and spirituality as providing a framework for recovery"; "religion and spirituality as offering key ingredients in the recovery process"; and "barriers to recovery through religion/spirituality". The first two themes highlight some of the positive aspects that aid participants' recovery. The third theme reported hindrances in participants' religious/spiritual practices and beliefs. Each theme is discussed with reference to sub-themes and illustrative excerpts. Practical implications: Religion/spirituality might support therapeutic engagement for some service users and staff could be more active in their enquiry of the value that patients place on the personal meaning of this for their life. Originality/value: For the participants in this study, religion/spirituality supported the principles of recovery, in having an identity separate from illness or offender, promoting hope, agency and personal meaning.